2000
DOI: 10.1108/14635770010331379
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking tax compliance efficiency (risk) at the business entity level

Abstract: Empirical works on examining taxpayer compliance and judiciously targeting risky taxpayers from a population of large taxpayers are hitherto scarce. This paucity of research has been the main result of the limited set of taxpaid data available at a micro level to researchers. It is in this context, the objective of this paper is to suggest a benchmarking method, which takes into account firm‐specific, particularly governance characteristics, to identify and measure the extent of taxpayer compliance with the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…There have been very few attempts in the literature to derive a economic model of profits (although Cowling and Waterson (1976) and Feeny et al (2005) are notable exceptions). However, this has not stopped a proliferation of many empirical profit functions being estimated (Intriligator, 1978; Domowitz et al 1986a, b; Kalirajan, 1993; Prince, 1994; Bhattacharya and Bloch, 1997; Syed and Kalirajan, 2000). In this paper, we predominantly follow the empirical literature in the specifications of the profit functions.…”
Section: Empirical Model Of Profitabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…There have been very few attempts in the literature to derive a economic model of profits (although Cowling and Waterson (1976) and Feeny et al (2005) are notable exceptions). However, this has not stopped a proliferation of many empirical profit functions being estimated (Intriligator, 1978; Domowitz et al 1986a, b; Kalirajan, 1993; Prince, 1994; Bhattacharya and Bloch, 1997; Syed and Kalirajan, 2000). In this paper, we predominantly follow the empirical literature in the specifications of the profit functions.…”
Section: Empirical Model Of Profitabilitymentioning
confidence: 99%
“…There have been numerous studies concerned with estimating stochastic frontier production functions, and from these estimated (relative) firm efficiencies (Battese and Coelli, 1988, 1995; Coelli, 1996; Feeny and Rogers, 2003). Indeed, in a related study, Syed and Kalirajan (2000) take a stochastic frontier production approach but applied to profit functions in order to benchmark tax compliance measures. However, all of these studies, including Syed and Kalirajan (2000), are invariably estimated using cross‐sectional data with various distributional assumptions made regarding the composite error term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gap in the literature in the area of corporate tax evasion has been pointed out both by scholars (Syed and Kalirajan, 2000;Chen and Chu, 2005;Crocker and Slemrod, 2005;Tedds, 2006) and international organizations (OECD, 2001). However, it must be taken into account that the lack of available data regarding the outcome of tax audits, and in some cases regarding even the level of taxable income itself (Hanlon, 2003), impedes relevant research.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of large accounting scandals, involving companies like Enron, WorldCom and Tyco, have shown that it is possible for the companies to evade taxes and at the same time to manipulate accounting earnings upwards by using tax shelters (Desai, 2005;Desai and Dharmapala, 2009). The gap in the literature in the area of corporate tax evasion has been pointed out both by scholars (Syed and Kalirajan, 2000;Chen and Chu, 2005;Crocker and Slemrod, 2005;Tedds, 2006) and international organizations (OECD, 2001). However, it must be taken into account that the lack of available data regarding the outcome of tax audits, and in some cases regarding even the level of taxable income itself (Hanlon, 2003), impedes relevant research.…”
Section: Introductionmentioning
confidence: 99%